Clinical and hormonal profile of patients diagnosed with polycystic ovarian syndrome at tertiary care hospital in Tamil Nadu - S., Sathiya; S., Renuka; M., Famida A.; J., Jennifer Britto; K., Vijayalakshmi; R., Sailatha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: In recent years due to the changing sedentary life style, irregular periods and infertility has become a major concern. There are many causes for infertility out of which ovulatory disorders contribute to a great extend. The main objective of the study was to assess the clinical and hormonal profile of patients diagnosed with polycystic ovarian disease at tertiary care hospital in Tamil Nadu. Methods: This study was a cross sectional study and was carried out at the Department of Obstetrics and Gynaecology at a tertiary care hospital of Tamil Nadu. The study was done for a period of 6 months. For confirming polycystic ovaries, patients were interviewed thoroughly about their menstrual and fertility history. Blood investigations like LH, FSH were done on D2/D3 of menstrual cycle. 125 patients with PCOS were included in this study. The data was analysed with SPSS-IBM (V.22.0) software. Results: The patients having polycystic ovaries were higher in women of 21-30 years of age. BMI was more than 25. Infertility was found that 57%, hirsutism 45%, oligomenorrhoea 21% and amenorrhea 20%. On day 2, mean serum LH was 5.9±3.6 and serum FSH was 3.9±2.3. This study showed that the proportion of menstrual complaints is reported more in higher age group. Likewise lower income group presented with menstrual complaints. This was found to be statistically significant (P value <0.05). Conclusions: The study showed that patients diagnosed to have PCOS overweight. PCO in obese women had more severe ovulatory dysfunction. Infertility was the most common complaint.